Comparison of the blood parameters with the chemical composition of the muscle tissue of meat-and-egg chicken - R. V. Nekrasov; N. V. Bogolyubova; A. A. Zelenchenkova; R. A. Rykov; N. A. Volkova; A. N. Vetokh (Теория и практика переработки мяса)
Basic blood and muscle tissue parameters have been analyzed in crossbred male Russian White and Cornish hens (♂, RW x CORN, n=95, slaughtered at 63 days of age). According to BW at slaughter, males (n=95) were divided into 3 groups (group 1–1,000–1,799 g, n=31; group 2–1,800–2,099 g, n=28; group 3–2,100–2,650 g, n=36). It has been found that with an increase in the live weight at slaughter, the ratio of albumin to globulin (p=0.038), aspartate aminotransferase (p=0.003) increased in the serum of birds; the levels of globulins (p=0.05), glucose (p=0.02), Ca (p=0.006), Mg (p=0.05) decreased. With increasing BW, the crude protein content in thigh muscle decreased (p=0.019) against a trend towards increasing moisture content in thigh meat (p=0.058). Comparative assessment of biochemical blood parameters of nitrogen, carbohydrate-lipid, mineral metabolism, antioxidant protection parameters, some clinical blood parameters (hematocrit, erythrocytes and hemoglobin) and chemical composition of the breast and thigh muscle tissue has been carried out. The analysis (Pearson correlation coefficients) has revealed patterns between the concentration of some blood metabolites and the composition of muscle tissue in males. Thus, the accumulation and analysis of data on resource genetic populations is of interest for science and practice in order to establish relationships between blood parameters and the quality of chicken products, as well as to identify biomarkers for predicting poultry productivity in vivo.